ChemInform Abstract: CsOH/γ‐Al2O3: A Heterogeneous Reusable Basic Catalyst for One‐Pot Synthesis of 2‐Amino‐4, 6‐diaryl Pyrimidines. Issue 29 (June 2016) - Nimkar, Amey; Ramana, M. M. V.; Betkar, Rahul; Ranade, Prasanna; Mundhe, Balaji
Abstract: The title pyrimidines are simply and efficiently synthesized by a green one‐pot three‐component reaction of acetophenone, various aromatic aldehydes, and guanidine hydrochloride using CsOH/γ‐Al2 O3 as catalyst.